26MG EXCESS IN HIBONITES OF THE RUMURUTI CHONDRITE HUGHES 030 - Bischoff A.; Srinivasan G. (My University, 2003)
The Rumuruti chondrites (R chondrites) constitute a new, well-established, chondrite group different from carbonaceous, ordinary, and enstatite chondrites. Most samples of this group are gas-rich regolith breccias showing the typical light/dark structure and consist of abundant fragments of various parent body lithologies embedded in a fine-grained, olivine-rich matrix. Most R chondrites contain the typical components of primitive chondrites including chondrules, chondrule and mineral fragments, sulfides, and rare calcium-aluminum-rich inclusions (CAIs). In Hughes 030, an interesting CAI consisting of abundant hibonite and spinel was found. Mg isotopic analyses revealed excess 26Mg in components of R chondrites for the first time. The hibonite grains with high Al/Mg values (∼1500 to 2600) show resolved 26Mg excess. The slope of the correlation line yields an initial 26Al/ 27Al = (1.4 ± 0.3) × 10−6, which is ∼40 times lower than the initial value measured in CAIs from primitive meteorites. The inferred difference in 26Al abundance implies a time difference of ∼4 million years for the closure of the Al-Mg system between CAIs from primitive chondrites and the Hughes 030 CAI. Based on mineralogy and the petrographic setting of the hibonite-rich CAI, it is suggested that 4 million years reflect the time interval between the formation of the CAI and the end of its secondary alteration. It is also suggested that most of this alteration may have occurred in the nebula (e.g. Zn- and Fe-incorporation in spinels). However, the CAI could not have survived in the nebula as a free floating object for a long period of time. Therefore, the possibility of storage in a precursor planetesimal for a few million years, resetting the magnesium-aluminum isotopic system, prior to impact brecciation, excavation, and accretion of the final R chondrite parent body cannot be ruled out.